Antibacterial silver-loaded nano zirconium phosphate / PPSU composite material and masterbatching preparation method thereof

CN122978710APending Publication Date: 2026-10-27ZHEJIANG MATERNAL LOVE BABIES ARTICLES CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611213853.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]针对现有抗菌PPSU复合材料中银活性组分添加量高、粉体易团聚、界面结合弱、高温熔融加工后抗菌功能分布不均,以及现有PP、PVC等抗菌材料技术难以直接适配PPSU高温高黏度加工体系的问题,本发明提出一种抗菌载银纳米磷酸锆/PPSU复合材料

Benefits of technology

1、通过磷酸锆载体锚定银活性组分,降低银活性组分在高温加工和长期使用中的团聚与局部富集风险。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978710A_ABST
    Figure CN122978710A_ABST
Patent Text Reader

Abstract

The application provides an antibacterial silver-loaded nanometer zirconium phosphate / PPSU composite material and a master batch preparation method thereof. The composite material comprises a PPSU resin matrix, a silver-loaded nanometer zirconium phosphate antibacterial agent dispersed in the PPSU resin matrix, and a compatible modification interface layer between the antibacterial agent and the PPSU resin; the silver-loaded nanometer zirconium phosphate antibacterial agent comprises at least one of flaky, needle-shaped or rod-shaped, cubic silver-loaded zirconium phosphate. The application designs a preparation method of "silver active component carrier anchoring-PPSU compatible interface layer-antibacterial functional master batch pre-dispersion-PPSU secondary dilution blending" for the application scenarios of PPSU high-temperature processing, high melt viscosity, light color appearance and repeated disinfection, can reduce the risk of nanometer agglomeration, local silver enrichment, color fluctuation and mechanical property loss in high-temperature melting processing, and can balance the antibacterial function, processing stability, appearance stability and mechanical property retention at a lower silver addition amount.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of polymer antibacterial composite materials and functional masterbatch preparation, specifically relating to an antibacterial silver-loaded zirconium phosphate / PPSU (polyphenylsulfone) composite material and its masterbatch preparation method, using PPSU as a high-performance resin matrix and silver-loaded zirconium phosphate as the antibacterial functional phase. The antibacterial composite material and its masterbatch preparation method are particularly suitable for antibacterial engineering plastic products that require high temperature resistance, repeated sterilization, and high standards for appearance and safety. Background Technology

[0002] PPSU possesses characteristics such as high temperature resistance, hydrolysis resistance, impact resistance, and good dimensional stability, and has been used in infant feeding products, drinking water components, medical device structural parts, and engineering plastic products that can be repeatedly steam sterilized. However, with increasing demands for public health and food contact materials, the heat resistance and mechanical properties of PPSU alone are no longer sufficient to meet the requirements for antibacterial functionalization.

[0003] Silver-based antibacterial materials have advantages such as broad spectrum, high efficiency, and low risk of drug resistance, and are widely used in plastics, rubber, coatings, fibers, and medical and food contact materials. However, if silver salts, nano-silver, or ordinary silver powders are directly added to PPSU, problems such as agglomeration, darkening of color, local silver enrichment, unstable dispersion during melt processing, and loss of mechanical properties often occur. In particular, PPSU has a high melt viscosity and a high processing temperature, making it difficult to ensure the uniform distribution of nano-antibacterial agents in the resin by ordinary dry mixing or single melt blending.

[0004] Existing antibacterial plastics or antibacterial masterbatch technologies are mostly concentrated on general-purpose plastics such as PP, PE, PVC, and PMMA, or relatively low-temperature processed materials. For example, some solutions use polypropylene chips and nano-silver powder to prepare polypropylene antibacterial masterbatches, while others target PP fibers, BOPP films, or PVC antibacterial plastics. There are also general-purpose inorganic antibacterial agent masterbatches that use binders to adhere the antibacterial material to the surface of the matrix resin particles. These technologies typically focus on solving the problem of adding antibacterial fillers or preparing masterbatches for general-purpose resins, but they do not address the overall design issues related to PPSU's high processing temperature, high melt viscosity, light-colored appearance retention, steam sterilization stability, and the anchoring and dispersion of silver active components in high-temperature melting environments.

[0005] Zirconium phosphate possesses good chemical stability, ion exchange capacity, and thermal stability, making it suitable as a support for silver ions or silver nanoparticles. Silver-loaded zirconium phosphate can utilize the ion exchange, interlayer structure, thermal stability, and inorganic support stability of zirconium phosphate to achieve the anchoring and sustained release of silver active components. However, existing silver-loaded zirconium phosphate materials still have shortcomings in terms of support morphology control, silver loading uniformity, and dispersion stability in different resin systems. When support particles agglomerate or the distribution of silver active components is uneven, it can easily lead to problems such as decreased antibacterial efficiency, product appearance defects, decreased mechanical properties, or unstable silver component migration during processing. In particular, simply adding silver-loaded zirconium phosphate as a common powder to PPSU still cannot solve the problems of insufficient interfacial compatibility and secondary agglomeration. Therefore, there is a need for an antibacterial PPSU composite material that differs from existing PP or other general-purpose antibacterial materials and is designed holistically around the PPSU-specific processing environment, considering "support morphology, silver anchoring, interfacial compatibility, and masterbatch dispersion." Summary of the Invention

[0006] To address the problems of high silver active component content, easy powder agglomeration, weak interfacial bonding, uneven distribution of antibacterial function after high-temperature melting processing in existing antibacterial PPSU composite materials, and the difficulty of directly adapting existing antibacterial materials such as PP and PVC to the high-temperature and high-viscosity processing system of PPSU, this invention proposes an antibacterial silver-loaded nano-zirconium phosphate / PPSU composite material.

[0007] Another object of the present invention is to provide a masterbatch preparation method for the antibacterial silver-loaded zirconium phosphate / PPSU composite material.

[0008] The objective of this invention is achieved through the following scheme: an antibacterial silver-loaded zirconium phosphate nanoparticle / PPSU composite material, comprising a PPSU resin matrix, a silver-loaded zirconium phosphate nanoparticle antibacterial agent dispersed in the PPSU resin matrix, and a compatibility-modified interface layer located on the surface of the silver-loaded zirconium phosphate nanoparticle antibacterial agent; the silver-loaded zirconium phosphate nanoparticle antibacterial agent comprises a zirconium phosphate carrier and a silver active component loaded on the surface, pores, or interlayer structure of the zirconium phosphate carrier; the silver-loaded zirconium phosphate nanoparticle antibacterial agent is distributed in the PPSU matrix in the form of discrete particles, sheets, or short rods, used to reduce the color deepening and performance fluctuations caused by local silver enrichment; by weight, it comprises at least 90-99.8 parts of PPSU resin, 0.05-5 parts of silver-loaded zirconium phosphate nanoparticle antibacterial agent, 0.1-5 parts of compatibility and dispersion aid, and 0-2 parts of heat-stabilizing aid.

[0009] The core innovations of this invention are as follows: First, a zirconium phosphate carrier is used to immobilize the silver active component, instead of directly adding free nano-silver; second, different loading sites and melt dispersion behaviors are provided by carriers with different morphologies such as sheet, needle, rod, and / or cubic; third, an interface modification layer compatible with PPSU is constructed on the surface of silver-loaded zirconium phosphate nanoparticles to reduce the interfacial energy between inorganic particles and high-viscosity PPSU melt; fourth, an antibacterial functional masterbatch pre-dispersion and dilution blending step is introduced to ensure that the antibacterial agent is uniformly distributed in the final PPSU matrix; fifth, it is designed for steam-sterilizable PPSU products, light-colored or semi-transparent products, taking into account antibacterial performance, color stability, silver migration control, and mechanical property retention.

[0010] Furthermore, the nano-zirconium phosphate support is one or more of sheet-like ZrP-1, needle-like or rod-like ZrP-2, and cubic ZrP-3; wherein the sheet-like support is used to provide interlayer silver loading sites, the needle-like or rod-like support is used to form an oriented dispersion structure in the melt shear field, and the cubic support is used to improve the stability of particle filling distribution.

[0011] Based on the above scheme, the silver active component exists in the form of silver ions, silver nanoparticles, or a combination of both, and is fixed on the nano-zirconium phosphate support by means of ion exchange, adsorption, complexation, or in-situ deposition.

[0012] Based on the above scheme, the compatibility-modified interface layer contains one or more of the following: silyl, amino, epoxy, aromatic, sulfone, ether bond structure or polyarylsulfone compatibility segment, which is used to reduce the interfacial energy between silver-loaded zirconium phosphate nanoparticles and PPSU melt and inhibit secondary agglomeration.

[0013] Based on the above scheme, the compatibility dispersant includes silane coupling agents, polysulfone oligomers, dispersants containing polar groups, high-temperature lubricants, maleic anhydride graft polymers, or combinations thereof.

[0014] The present invention also provides a method for preparing the above-mentioned antibacterial silver-loaded zirconium phosphate nanoparticle / PPSU composite material. The silver-loaded zirconium phosphate antibacterial agent is first prepared into an antibacterial functional masterbatch with a compatibility dispersant and a portion of PPSU carrier resin, such that the mass content of the silver-loaded zirconium phosphate antibacterial agent in the antibacterial functional masterbatch is 5-40%. The antibacterial functional masterbatch is melt-diluted and blended with a certain amount of PPSU matrix resin according to a set ratio to obtain a PPSU composite material. The mass content of the silver-loaded zirconium phosphate antibacterial agent in the final PPSU composite material is 0.1-3.0%.

[0015] Furthermore, the preparation method includes the following steps: S1. Dehumidify and dry the PPSU resin; S2. Compatibility modification and pre-dispersion of silver-loaded nano-zirconium phosphate antibacterial agent; S3. Prepare antibacterial functional masterbatch by combining pre-dispersed antibacterial agent, compatibility dispersant and part of PPSU resin; S4. The antibacterial masterbatch is premixed with the remaining PPSU resin in a certain proportion to obtain a premix. S5. The premixed material was melt-blended by twin screw extruder, extruded and cooled, and pelletized and dried to obtain antibacterial silver-loaded nano-zirconium phosphate / PPSU composite material.

[0016] In S1, the drying temperature of the PPSU resin is 120-180℃ and the drying time is 2-8 h. In S5, the twin-screw melt blending adopts segmented temperature control, with a barrel temperature of 300-390℃ and a screw speed of 50-500 rpm. The secondary agglomeration of silver-loaded nano-zirconium phosphate in the PPSU melt is reduced by first low-shear plasticizing, then dispersion mixing, and then homogenization metering.

[0017] This invention also provides the application of the aforementioned antibacterial silver-loaded nano-zirconium phosphate / PPSU composite material in the preparation of antibacterial injection molded parts, food contact parts, infant product parts, drinking water system parts, steam sterilizable structural parts, or medical device-related plastic parts.

[0018] A silver-loaded zirconium phosphate nanoparticle antibacterial agent for use in antibacterial silver-loaded zirconium phosphate nanoparticle / PPSU composite materials includes the following preparation steps: 1) Prepare nano-zirconium phosphate support, wherein the nano-zirconium phosphate support includes at least one of sheet-like zirconium phosphate ZrP-1, needle-like or rod-like zirconium phosphate ZrP-2, and cubic zirconium phosphate ZrP-3; 2) Disperse the nano-zirconium phosphate support in deionized water. The amount of nano-zirconium phosphate support is 15-25g, and the amount of deionized water is 150-250mL. Heat the water to 55-75℃. 3) Add silver nitrate solution to the dispersion system and keep it at a warm temperature for reaction. The concentration of silver nitrate solution is 0.05-0.2 mol / L, the amount is 80-150 mL, the reaction temperature is 60-70℃, and the reaction time is 3-6 h, so that the silver active component is loaded on the surface, pores or interlayer structure of the nano-zirconium phosphate support. 4) The obtained silver-loaded nano-zirconium phosphate antibacterial agent Ag-ZrP was obtained by filtration, washing and drying.

[0019] The preparation of the flaky zirconium phosphate ZrP-1 includes: adding 15-18 g of zirconium oxychloride octahydrate, 20-30 g of oxalic acid and 15-22 mL of phosphoric acid sequentially to 300-400 mL of deionized water, stirring the mixture at 25-35℃ and 200-300 rpm for 2-4 h, allowing it to stand for 2-4 days, and then filtering, washing and drying at 70-90℃ to obtain flaky zirconium phosphate ZrP-1.

[0020] The preparation of the needle-shaped or rod-shaped zirconium phosphate ZrP-2 includes: adding 15-18 g of zirconium oxychloride octahydrate, 20-30 g of oxalic acid, 6-12 mL of phosphoric acid and 10-16 g of ethylenediamine sequentially to 300-400 mL of deionized water, stirring and reacting at 25-35℃ and 200-300 rpm for 2-4 h, followed by filtration, washing and drying at 70-90℃ to obtain needle-shaped or rod-shaped zirconium phosphate ZrP-2.

[0021] The preparation of cubic zirconium phosphate ZrP-3 includes: adding 15-18 g of zirconium oxychloride octahydrate, 5-9 g of oxalic acid and 8-13 g of diammonium hydrogen phosphate sequentially to 300-400 mL of deionized water, stirring and reacting at 65-85℃ and 200-300 rpm for 2-4 h, then transferring to a polytetrafluoroethylene reactor, reacting at 130-170℃ for 6-12 h, and then filtering, washing and drying at 70-90℃ to obtain cubic zirconium phosphate ZrP-3.

[0022] Unique features compared to other existing antimicrobial material solutions: I. Different substrates: This invention uses PPSU as the substrate and is designed for products that require high-temperature processing, repeated sterilization, and high appearance requirements.

[0023] II. Different Antibacterial Agent Structures: This invention uses silver-loaded nano-zirconium phosphate to anchor the silver active component on the surface, pores, or interlayer structure of the zirconium phosphate carrier, thereby reducing the aggregation and local enrichment of free silver.

[0024] Third, different dispersion paths: This invention forms a multi-level dispersion path through a compatibility-modified interface layer, antibacterial functional masterbatch, and secondary dilution and blending of PPSU.

[0025] IV. Different performance objectives: This invention simultaneously considers the color stability of PPSU, resistance to high temperature hydrolysis, steam sterilization, low-addition antibacterial properties, and consistency of injection molded products.

[0026] V. Different Morphology Control: This invention uses plate-shaped, needle-shaped, rod-shaped, or cubic silver-loaded zirconium phosphate as selectable or compoundable functional phases, and utilizes the interlayer loading, shear orientation, and particle filling stabilization effects corresponding to different morphologies to enhance the adjustability of the formulation.

[0027] Beneficial effects 1. By anchoring the silver active component with a zirconium phosphate support, the risk of aggregation and local enrichment of the silver active component during high-temperature processing and long-term use is reduced.

[0028] 2. Improving the interfacial bonding between silver-loaded nano-zirconium phosphate and PPSU segments through a compatibility-modified interface layer is beneficial for maintaining the material's impact strength, transparency, or color stability.

[0029] 3. By using antibacterial masterbatch and secondary dilution blending, the accuracy of antibacterial agent metering and dispersion stability are improved, making it suitable for subsequent injection molding and batch production.

[0030] 4. By compounding carriers with different morphologies, the structure of functional fillers can be adjusted according to the requirements of antibacterial properties, mechanical properties, product appearance and silver migration control.

[0031] 5. Compared with conventional antibacterial materials such as PP, PE, and PVC, this invention is more suitable for high-temperature, high-viscosity melt processing of PPSU and steam sterilization applications. Attached Figure Description

[0032] Figure 1 A schematic diagram illustrating the masterbatch dispersion principle of antibacterial nano-silver / PPSU composite material; Figure 2 Schematic diagram of the preparation routes for nano-zirconium phosphate supports with different morphologies; Figure 3 A schematic diagram of the interfacial compatibility and anchoring mechanism between silver-loaded zirconium phosphate and PPSU segments; Figure 4 A schematic diagram illustrating the structure-performance synergy principle of the antibacterial nano-silver / PPSU composite material; Figure 5 This is a schematic diagram of the preparation process of the silver-loaded nano-zirconium phosphate antibacterial agent of the present invention; Figure 6 The crystal morphology of the silver active component of this invention after being loaded onto a nano-zirconium phosphate support and then blended with PPSU is shown. Detailed Implementation

[0033] Example 1: Preparation of sheet-like nano-zirconium phosphate ZrP-1 supports; 16.1 g of zirconium oxychloride octahydrate, 25.2 g of oxalic acid, and 18 mL of phosphoric acid were added sequentially to 350 mL of deionized water. The mixture was stirred at 30 °C and 250 rpm for 3 h, allowed to stand for 3 days, and then filtered, washed, and dried at 80 °C to obtain nanosheet-like zirconium phosphate, named ZrP-1. (See [link to article]). Figure 2 .

[0034] Example 2: Preparation of needle-shaped or rod-shaped nano-zirconium phosphate ZrP-2 supports; 16.1 g of zirconium oxychloride octahydrate, 25.2 g of oxalic acid, 8.4 mL of phosphoric acid, and 13.5 g of ethylenediamine were added sequentially to 350 mL of deionized water. The mixture was stirred at 30 °C and 250 rpm for 3 h. After filtration, washing with deionized water, and drying at 80 °C, needle-like or rod-shaped zirconium phosphate was obtained, named ZrP-2. See [link to relevant documentation] Figure 2 .

[0035] The addition of ethylenediamine helps to control the crystal growth direction, resulting in zirconium phosphate exhibiting a needle-like or rod-like morphology that is distinct from that of the sheet-like support.

[0036] Example 3: Preparation of cubic zirconium phosphate nano-support ZrP-3: 16.9 g of zirconium oxychloride octahydrate, 6.61 g of oxalic acid, and 10.4 g of diammonium hydrogen phosphate were added sequentially to 350 mL of deionized water. The mixture was stirred at 75 °C and 250 rpm for 3 h. The reaction solution was then transferred to a polytetrafluoroethylene (PTFE) reactor and reacted at 150 °C for 9 h. Finally, the mixture was filtered, washed with deionized water, and dried at 80 °C to obtain cubic zirconium phosphate nano-support, named ZrP-3. (See...) Figure 2 .

[0037] Example 4: A silver-loaded nano-zirconium phosphate antibacterial agent Ag / ZrP, the process is as follows: Figure 5 As shown, prepare according to the following steps: 1) Take 20 g of each of the polymorphic zirconium phosphate nanocarriers ZrP-1, ZrP-2, and / or ZrP-3 prepared in Examples 1-3, add them to 200 mL of deionized water, stir to disperse, and heat to 65 °C to disperse in the deionized water; subsequently, 2) Add 113 mL of 0.1 mol / L silver nitrate solution; 3) Maintain the reaction at 65℃ for 4 h to allow silver ions or nano-silver active components to be loaded onto the zirconium phosphate support through ion exchange, adsorption or complexation. 4) After the reaction is complete, the silver-loaded zirconium phosphate antibacterial agents with different morphologies are obtained by filtration, washing with deionized water and drying.

[0038] Depending on the requirements of subsequent products regarding color, antibacterial efficiency, and mechanical properties, either a single-morphology carrier or a multi-morphology composite carrier can be used. The antibacterial agents obtained by using different carrier morphologies can be designated as Ag / ZrP-1, Ag / ZrP-2, and Ag / ZrP-3, respectively. These antibacterial agents can be used alone or in combination at certain mass ratios to comprehensively optimize dispersibility, silver release stability, and resin processing adaptability.

[0039] One or more of the following are selected as zirconium phosphate supports: sheet-like ZrP-1, needle-like or rod-like ZrP-2, and cubic ZrP-3. The silver active component is loaded onto the surface, pores, or interlayer structure of the support by reacting with silver nitrate solution.

[0040] Example 5: The masterbatch dispersion principle of antibacterial nano-silver / PPSU composite material is as follows: Figure 1As shown, multimorphic Ag / ZrP is modified at the interface to form a PPSU compatible interface layer. Masterbatch preparation and secondary dilution are then carried out to obtain a low-silver-content, uniformly dispersed antibacterial nano-silver / PPSU composite material.

[0041] Interface modification and pre-dispersion form a compatible modified interface layer The silver-loaded zirconium phosphate antibacterial agent Ag / ZrP prepared in Example 4 was pre-dispersed with a silane coupling agent, a polysulfone compatibility agent, or a dispersant containing polar groups to form a compatibility-modified interface layer on the surface of the antibacterial agent. This interface layer reduces secondary aggregation between the silver-loaded zirconium phosphate nanoparticles and enhances the interaction between them and PPSU segments. The interfacial compatibility and anchoring mechanism between the silver-loaded zirconium phosphate and PPSU segments is as follows: Figure 3 As shown; the structure-property synergistic principle of the antibacterial nano-silver / PPSU composite material is as follows: Figure 4 As shown; Preparation of antibacterial functional masterbatch Pre-dispersed silver-loaded zirconium phosphate nanoparticles were mixed at high speed with a portion of PPSU carrier resin, compatibility dispersant, and heat stabilizer, and then melt-blended using a twin-screw extruder to prepare an antibacterial masterbatch. The preferred antibacterial agent content in the masterbatch was 5-40% by mass, allowing for proportional dilution and addition during subsequent injection molding or melt blending. Preparation of antibacterial PPSU composite granules Antibacterial masterbatch was premixed with PPSU matrix resin in a certain proportion, and the final silver-loaded nano-zirconium phosphate content was controlled to be 0.1-3.0 wt%. The mixture was then subjected to twin-screw melt mixing, extrusion cooling, pelletizing, and drying to obtain antibacterial PPSU composite granules. Segmented temperature and moderate shearing were used during processing to avoid thermal degradation of PPSU and localized agglomeration of the antibacterial agent. The crystal morphology of the silver active component loaded onto the nano-zirconium phosphate carrier and blended with PPSU in this invention is as follows: Figure 6 As shown.

[0042] Comparative example: Comparison with conventional PP antibacterial masterbatch solutions To demonstrate the difference between this invention and ordinary PP or other general-purpose resin antibacterial masterbatches, comparative samples can be set up: Comparative sample A is an ordinary nano-silver / PPSU direct dry-melt blend system; Comparative sample B is an unmodified silver-loaded zirconium phosphate / PPSU system; the sample of this invention is a compatibility-modified silver-loaded zirconium phosphate antibacterial masterbatch / PPSU secondary dilution blend system. SEM / EDS dispersion state, color change, antibacterial rate, impact strength, melt flowability, and silver migration are compared to verify the effects of interface modification and masterbatch dispersion on the PPSU system.

[0043] Optional performance evaluation The resulting composite material can be evaluated using SEM / EDS dispersion observation, silver content testing, antibacterial rate testing, silver migration testing, tensile strength, impact strength, heat distortion temperature, melt flowability, color change, and transparency. If molecular dynamics simulations are introduced, a PPSU / Ag-ZrP interface model can be established to analyze binding energy, RDF, MSD, free volume, and virtual tensile stress-strain curves, thereby explaining the influence of interfacial compatibility on mechanical properties. .

Claims

1. An antibacterial silver-loaded nano-zirconium phosphate / PPSU composite material, characterized in that, The product comprises a PPSU resin matrix, a silver-loaded zirconium phosphate antibacterial agent dispersed in the PPSU resin matrix, and a compatibility-modified interface layer on the surface of the silver-loaded zirconium phosphate antibacterial agent. The silver-loaded zirconium phosphate antibacterial agent includes a zirconium phosphate carrier and a silver active component loaded on the surface, pores, or interlayer structure of the zirconium phosphate carrier. The silver-loaded zirconium phosphate antibacterial agent is distributed in the PPSU matrix in the form of discrete particles, sheets, or short rods. It is used to reduce the color deepening and performance fluctuation caused by local silver enrichment. By weight, it comprises at least 90-99.8 parts of PPSU resin, 0.05-5 parts of silver-loaded zirconium phosphate antibacterial agent, 0.1-5 parts of compatibility and dispersion aid, and 0-2 parts of heat stabilizing aid.

2. The antibacterial silver-loaded zirconium phosphate / PPSU composite material according to claim 1, characterized in that, The nano-zirconium phosphate support is one or more of sheet-like ZrP-1, needle-like or rod-like ZrP-2, and cubic ZrP-3; wherein the sheet-like support is used to provide interlayer silver loading sites, the needle-like or rod-like support is used to form an oriented dispersion structure in the melt shear field, and the cubic support is used to improve the stability of particle filling distribution.

3. The antibacterial silver-loaded zirconium phosphate / PPSU composite material according to claim 1, characterized in that, The silver active component exists in the form of silver ions, silver nanoparticles, or a combination of both, and is fixed on the nano-zirconium phosphate support by means of ion exchange, adsorption, complexation, or in-situ deposition.

4. The antibacterial silver-loaded zirconium phosphate / PPSU composite material according to claim 1, characterized in that, The compatibility-modified interface layer contains one or more of the following: silyl, amino, epoxy, aromatic, sulfone, ether bond structure or polyarylsulfone compatibility segment, used to reduce the interfacial energy between silver-loaded zirconium phosphate nanoparticles and PPSU melt and to inhibit secondary agglomeration.

5. The antibacterial silver-loaded zirconium phosphate / PPSU composite material according to claim 1, characterized in that, The compatibility and dispersibility aids include silane coupling agents, polysulfone oligomers, dispersants containing polar groups, high-temperature lubricants, maleic anhydride graft polymers, or combinations thereof.

6. A method for preparing an antibacterial silver-loaded zirconium phosphate / PPSU composite material according to any one of claims 1 to 5, characterized in that, The silver-loaded nano-zirconium phosphate antibacterial agent is first prepared into an antibacterial functional masterbatch with a compatibility dispersant and a portion of PPSU carrier resin, such that the mass content of the silver-loaded nano-zirconium phosphate antibacterial agent in the antibacterial functional masterbatch is 5-40%. The antibacterial functional masterbatch is melt-diluted and blended with a certain amount of PPSU matrix resin according to a set ratio to obtain a PPSU composite material, wherein the mass content of the silver-loaded nano-zirconium phosphate antibacterial agent in the final PPSU composite material is 0.1-3.0%.

7. The preparation method according to claim 6, characterized in that, Includes the following steps: S1. Dehumidify and dry the PPSU resin; S2. Compatibility modification and pre-dispersion of silver-loaded nano-zirconium phosphate antibacterial agent; S3. Prepare antibacterial functional masterbatch by combining pre-dispersed antibacterial agent, compatibility dispersant and part of PPSU resin; S4. The antibacterial masterbatch is premixed with the remaining PPSU resin in a certain proportion to obtain a premix. S5. The premixed material was melt-blended by twin screw extruder, extruded and cooled, and pelletized and dried to obtain antibacterial silver-loaded nano-zirconium phosphate / PPSU composite material.

8. The preparation method according to claim 7, characterized in that, In S1, the drying temperature of the PPSU resin is 120-180℃, and the drying time is 2-8 h; in S5, the twin-screw melt blending adopts segmented temperature control, with a barrel temperature of 300-390℃ and a screw speed of 50-500 rpm, and adopts a method of first low-shear plasticizing, then dispersion mixing, and then homogenization metering to reduce the secondary agglomeration of silver-loaded nano-zirconium phosphate in the PPSU melt.

9. The application of the antibacterial silver-loaded nano-zirconium phosphate / PPSU composite material according to any one of claims 1 to 5 in the preparation of antibacterial injection molded parts, food contact parts, infant product parts, drinking water system parts, steam sterilizable structural parts or medical device related plastic parts.

10. A method for preparing a silver-loaded zirconium phosphate nanoparticle antibacterial agent, used in antibacterial silver-loaded zirconium phosphate nanoparticle / PPSU composite materials, characterized in that, The preparation steps include the following: 1) Prepare nano-zirconium phosphate support, wherein the nano-zirconium phosphate support includes at least one of sheet-like zirconium phosphate ZrP-1, needle-like or rod-like zirconium phosphate ZrP-2, and cubic zirconium phosphate ZrP-3; 2) Disperse the nano-zirconium phosphate support in deionized water. The amount of nano-zirconium phosphate support is 15-25 g, and the amount of deionized water is 150-250 mL. Heat the water to 55-75℃. 3) Add silver nitrate solution to the dispersion system and keep it at a warm temperature for reaction. The concentration of silver nitrate solution is 0.05-0.2 mol / L, the amount is 80-150 mL, the reaction temperature is 60-70℃, and the reaction time is 3-6 h, so that the silver active component is loaded on the surface, pores or interlayer structure of the nano-zirconium phosphate support. 4) After filtration, washing and drying, silver-loaded nano-zirconium phosphate antibacterial agent is obtained.

11. The method for preparing the silver-loaded nano-zirconium phosphate antibacterial agent according to claim 10, characterized in that, The preparation of the flaky zirconium phosphate ZrP-1 includes: adding 15-18 g of zirconium oxychloride octahydrate, 20-30 g of oxalic acid and 15-22 mL of phosphoric acid sequentially to 300-400 mL of deionized water, stirring the mixture at 25-35℃ and 200-300 rpm for 2-4 h, allowing it to stand for 2-4 days, and then filtering, washing and drying at 70-90℃ to obtain flaky zirconium phosphate ZrP-1.

12. The method for preparing the silver-loaded nano-zirconium phosphate antibacterial agent according to claim 11, characterized in that, To prepare zirconium phosphate flakes ZrP-1, 16.1 g of zirconium oxychloride octahydrate, 25.2 g of oxalic acid, and 18 mL of phosphoric acid were added sequentially to 350 mL of deionized water. The mixture was stirred at 30 °C and 250 rpm for 3 h, allowed to stand for 3 days, and then filtered, washed, and dried at 80 °C to obtain ZrP-1.

13. The method for preparing the silver-loaded nano-zirconium phosphate antibacterial agent according to claim 10, characterized in that, The preparation of the needle-shaped or rod-shaped zirconium phosphate ZrP-2 includes: adding 15-18 g of zirconium oxychloride octahydrate, 20-30 g of oxalic acid, 6-12 mL of phosphoric acid and 10-16 g of ethylenediamine sequentially to 300-400 mL of deionized water, stirring and reacting at 25-35℃ and 200-300 rpm for 2-4 h, followed by filtration, washing and drying at 70-90℃ to obtain needle-shaped or rod-shaped zirconium phosphate ZrP-2.

14. The method for preparing the silver-loaded nano-zirconium phosphate antibacterial agent according to claim 13, characterized in that, To prepare needle-shaped or rod-shaped zirconium phosphate (ZrP-2), 16.1 g of zirconium oxychloride octahydrate, 25.2 g of oxalic acid, 8.4 mL of phosphoric acid, and 13.5 g of ethylenediamine were added sequentially to 350 mL of deionized water. The mixture was stirred at 30 °C and 250 rpm for 3 h. After filtration, washing, and drying at 80 °C, ZrP-2 was obtained.

15. The method for preparing the silver-loaded nano-zirconium phosphate antibacterial agent according to claim 10, characterized in that, The preparation of cubic zirconium phosphate ZrP-3 includes: adding 15-18 g of zirconium oxychloride octahydrate, 5-9 g of oxalic acid and 8-13 g of diammonium hydrogen phosphate sequentially to 300-400 mL of deionized water, stirring and reacting at 65-85℃ and 200-300 rpm for 2-4 h, then transferring to a polytetrafluoroethylene reactor, reacting at 130-170℃ for 6-12 h, and then filtering, washing and drying at 70-90℃ to obtain cubic zirconium phosphate ZrP-3.

16. The antibacterial silver-loaded zirconium phosphate / PPSU composite material according to claim 15, characterized in that, To prepare cubic zirconium phosphate (ZrP-3), 16.9 g of zirconium oxychloride octahydrate, 6.61 g of oxalic acid, and 10.4 g of diammonium hydrogen phosphate were added sequentially to 350 mL of deionized water. The mixture was stirred at 75 °C and 250 rpm for 3 h. Then, the mixture was transferred to a polytetrafluoroethylene (PTFE) reactor and reacted at 150 °C for 9 h. After filtration, washing, and drying at 80 °C, ZrP-3 was obtained.